Social Media and the Formation of Political Knowledge of Generation Z Students - Wina Tricahyani Sianturi; Monalisa Simbolon; Ninda Theresia Sipayung; Mastyana Siburian; Sthephany Nababan; Dian Rahmat Siregar (Civiliza Publishing, Indonesia., 2026)
The development of social media has changed the consumption patterns of political information among the younger generation, especially Generation Z students. This study aims to analyze how social media is utilized as a source of political information and how this utilization shapes the political knowledge of students at HKBP Nommensen University, Pematangsiantar. This study used a descriptive qualitative approach with data collection techniques in the form of semi-structured interviews with nine Generation Z students from several study programs. Interviews were conducted in January-February 2026 with a duration of 5–10 minutes for each informant. Data were analyzed using thematic analysis through the stages of transcription, open coding, grouping themes, and data interpretation. The results show that TikTok, Instagram, YouTube, Facebook, and X/Twitter are the main platforms for accessing political information because they are considered fast, practical, and easy to access. Social media is perceived not only as a source of information, but also as a digital communication space that shapes students' political knowledge, opinions, and critical attitudes. However, the depth of political knowledge formed is still influenced by digital literacy, academic environment, peers, and social experiences. This study confirms that social media plays a role as an informal political learning space for Generation Z students.